Exit, voice, and ethics - Keeley, Michael (Journal of business ethics, 1991)
Hirschman's (1970) exit, voice, and loyalty framework draws attention to both economic and political behavior as instruments for organizational change. The framework is simple but powerful; it has stimulated much cross-disciplinary analysis and debate. This paper extends this analysis by examining normative implications of Hirschman's basic premise: that exit and voice are primarily mechanisms for enhancing organizational (vs. individual) well-being.